EFEK RUMINASI PADA REMAJA YANG MENGALAMI KESULITAN MOVE ON - Mudya Putri, Khoirunisa Az-Zahra; Ramadhan, Fauzan Nazil; Maharani, Anisa; Rosuly, Rindu; Ramanda, Peni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to understand more deeply about the difficulty of moving on in adolescents after a breakup, especially related to rumination. The phenomenon of a breakup often causes individuals to have difficulty moving on whichcan trigger psychological problems such as rumination, anxiety, self-concept confusion, and identity crisis. Rumination as a process of thinking repeatedly about negative experieces in the past, was found to help mental-emotional conditions and inhibit recovery. This study used a qualitative approach with semi-structured in-depth interviews with single participants (SNA) who had difficulty moving on after the end of a three-year relationship. Data analysis was inductive using thematic analysis. The results showed that SNA experienced intense emotional rumination, prolonged anxiety, emotional dependence, and self-concept confusion after a breakup. These findings confirm that ruminating prolongs emotional stress and inhibits psychological recovery. This study is expected to contribute to finding effective strategies to overcome the impact of insight into healthier ways of dealing with the past.